Efficient biosorption of hexavalent chromium from water by modified arecanut leaf sheath. Issue 4 (April 2022) - Pant, Bishnu Datt; Neupane, Deepa; Paudel, Dasu Ram; Chandra Lohani, Prakash; Gautam, Surendra Kumar; Pokhrel, Megh Raj; Poudel, Bhoj Raj
Abstract: In this work, the excision of hexavalent chromium (Cr(VI)) was studied from an aqueous solution using the chemically modified arecanut leaf sheath (CALS) as a novel bio-adsorbent. The as-prepared adsorbent was characterized by using instrumental methods including Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS). The effect of several factors, including solution pH, contact time, and sorbent dosages were examined to identify the optimum condition for the sorption ability. The optimal pH of Cr(VI) biosorption was 2.0, and equilibrium was reached in 150 min. Adsorption was shown to be pseudo-second-order in kinetic investigations, and the Langmuir isotherm with maximal adsorption efficiency was determined as 109.89 mg/g. The spent biosorbent can be easily regenerated and reused. For the biosorption of oxyanions of chromium, both electrostatic attraction and ligand exchange mechanism play critical roles. From the results, the CALS appears to be a potential low-cost effective sorbent to remove Cr (VI) from water. Abstract : Cr(VI); Biosorbent, CALS, Adsorption isotherms, Kinetics.